Movement of Spodoptera frugiperda Adults (Lepidoptera: Noctuidae) in Maize in Brazil - Vilarinho, Elis Cristine [UNESP]; Fernandes, Odair Aparecido [UNESP]; Hunt, Thomas E.; Caixeta, Daniel Ferreira [UNESP] (Florida Entomological Soc, 2011)
The fall armyworm, Spodoptera frugiperda (J. E. Smith), is one of the most important maize pests in the Americas and particularly in South America. With the adoption of genetically modified plants expressing Bacillus thuringiensis toxins for lepidopterous pest control, there is a need for establishing strategies to delay the development of insect resistance (e.g. refuge areas). Thus, information on target insects' dispersal is essential to improve pest management techniques. The objective of this work was to evaluate the dispersal capacity of S. frugiperda adults using mark-release-recapture techniques. Insects were marked using red oil-soluble dye in the larval artificial diet. Marked adults were released twice in each growing season (dry and wet) in southeastern Brazil in 2006 and 2007. Recapture of marked insects was performed using light and pheromone traps. Males are more attracted to light traps than females and the recapture rate was higher in the dry season than in the rainy season. The most adequate model to explain the relationship between flight distance and number of recaptured insects is y = a(2)/ (1+ (2a(1.8)+ bx))((2.6)), where y is the distance and x is the number captured. The maximum recapture distances were 806 m for males and 608 m for females. Therefore, strategies for establishment of refuges should take such distances into consideration.
Keywords: Fall armyworm; Release - recapture; Insect dispersal; Insect resistance